Pelatihan Perbendaharaan Gereja Jemaat GPI Papua Ebenhaezer Fakfak Klasis GPI Papua Fakfak - Fafan Titaley, Meiske Marisa (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The purpose of this devotional is to impart knowledge to congregational treasurers, categorical vessels and auxiliary bodies on the importance of financial recording in church financial management. Approach techniques carried out were seminars and simulations or face-to-face training. It is hoped that this dedication will impact the members of the GPI Papua Fakfak congregation namely improvement on church finances and the application of financial recording to achieve financial management transparency.